Effect Of Profitability And Price Earning Ratio On The Value Of Manufacturing Companies Listed On The Indonesia Stock Exchange In 2020-2023 - Muhamad Aulia Yahya; Nelly Martini (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the effect of profitability and price earning ratio (PER) on the value of manufacturing companies listed on the Indonesia Stock Exchange during the 2020-2023 period. Methodology: The data used in this study was obtained from the annual financial statements of 20 manufacturing companies selected as samples. The analysis method used was multiple regression analysis with company value as dependent variables and profitability, PER, company size, leverage, and sales growth as independent variables. Results: The results show that profitability and PER have a positive and significant influence on the company's value, while the size of the company has a positive effect and leverage has a negative effect on the company's value. Findings: These findings support signaling theory and trade-off theory, and are consistent with some previous research. Novelty & Originality: The novelty of this study lies in its comprehensive examination of multiple financial determinants within a single analytical framework focusing on the manufacturing sector during the post-pandemic recovery period of 2020-2023. Its originality emerges from the integrated application of both signaling theory and trade-off theory to explain firm value in an emerging market setting. Conclusions: The implication of this study is that investors and company managers can consider these factors in making investment decisions and formulate strategies to increase the value of the company. Type of Paper: This paper is an empirical research paper